Screening teams of moral and altruistic agents - Roberto Sarkisian (Games, 2021)
This paper studies the problem of screening teams of either moral or altruistic agents, in a setting where agents choose whether or not to exert effort in order to achieve a high output for the principal. I show that there exists no separating equilibrium menu of contracts that induces the agents to reveal their types unless the principal either (i) excludes one group from the productive relationship, or (ii) demands different efforts from different preference groups. I also characterize the contract-inducing pooling equilibria in which all agents are incentivized to exert a high level of effort.
Keywords: D82; D86; D03; 330; altruism; homo moralis; screening